To the theory of spatially nonuniform Bose systems with broken symmetry - Poluektov, Yu.M. (Вопросы атомной науки и техники, 2001)
The model of the self-consistent field for spatially nonuniform many-particle Bose-systems with broken symmetry is constructed. The self-consistent coupled equations for wave functions of the quasiparticles and of the particles of a condensate, and also system of the equations for normal and anomalous one-particle of density matrixes are deduced. The many-particle wave function is found. The thermodynamic of many-particle Bose-system on the basis of microscopic consideration in the self-consistent field model is constructed. We emphasize on the essential distinction of states with a Bose-condensate in model of ideal gas and in system of interating Bose-particles caused by obligatory presence alongside with one-particle, also of pair condensate, even at anyhow weak interaction.